Women’s empowerment in livestock sector as a tool to enhance child’s nutrition: a review - Fatema Tuj Zohora Hira; Mohammad Jahangir Alam; Ismat Ara Begum (Discover Sustainability)
Abstract The Women empowerment in the livestock sector has been emerged globally for assessing empowerment to promote sustainable development. This study aims to conduct a comprehensive review of existing literature on the interconnections among women’s empowerment in the livestock sector, child nutrition, and livestock interventions. Utilizing the PRISMA Protocol 2020, our research considers diverse factors such as nutritional status and interventions through livestock, in conjunction with women’s empowerment. We utilized major accessible electronic databases, including Google Scholar, PubMed, and relevant article references, as our data sources. Employing the PICO criteria and Boolean search technique, our study synthesizes published works, explores key concepts, and evaluates the strengths and weaknesses of various studies. Our findings reveal that women’s empowerment is context-specific, and many studies do not encompass all dimensions of WE in the livestock sector. While the Women’s Empowerment in Agriculture Index is widely employed in various contexts, there remains a need to further explore WE in the livestock sector. Moreover, our review highlights a narrow focus on livestock interventions in the existing literature. Although some studies explore the relationship between nutritional status and empowerment, only a limited number of studies examine the nexus among child nutritional status, livestock intervention, and empowerment. However, due to the limited studies conducted, a strong connection among these variables could not be firmly established. Consequently, our review underscores the substantial potential for a more comprehensive understanding of these interconnections. By elucidating the concepts and linkages among women’s empowerment, child nutrition, and livestock interventions, our study contributes to enhanced knowledge and identifies avenues for future research and policy implications.